A Rare Case of Functional Metastatic Follicular Thyroid Carcinoma With Concomitant Thyrotoxicosis - Yun Ann Chin; Zaheer Sumbul; Yi Lin Teh; Chiaw Ling Chng (Case Reports in Endocrinology)
We report a case of a 60-year-old lady with metastatic follicular thyroid carcinoma (FTC) who was presented with thyrotoxicosis and heart failure symptoms after total thyroidectomy. Clinical features and investigations led to the diagnosis of functional metastatic FTC with concomitant thyrotoxicosis. Levothyroxine therapy was stopped, and she was treated with propylthiouracil (PTU) followed by serial radioiodine treatments (RAITs) with good control of thyrotoxicosis and metastases. Despite having a very high disease burden with metastatic FTC, she has been able to maintain her functional status thus far, 4.5 years after initial diagnosis.